2018
DOI: 10.1515/erj-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

How Do Institutions Relate to Entrepreneurship: an Integrative Model

Abstract: This article brings together existing literature on institutions and entrepreneurship. Despite a recent increase in publications on their relationship, this line of inquiry is still very fragmented due to a lack of consistent theoretical framework to guide the selection of institutions. To provide a “big picture” of this research area, an integrative model is proposed around two central themes: theoretical constructs of institutions that work at different levels and their relationship with different aspects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
1
10
0
2
Order By: Relevance
“…Urbano et al (2019b), for instance, identify that existing scholarship tends more often to investigate variables such as taxes, property rights, contracts, and political factors related to freedom. Zhai et al (2019) complement this view by observing that cultural values, networks, cognitive factors and market dynamics are, among others, the most frequent (informal) institutions that scholars examine. Based on these literature reviews, it is suggested that variables related to the environment that affects the entrepreneurial process, in which proxies for the five dimensions that Gnyawali and Fogel (1994) suggest, need further attention.…”
Section: Institutional Environment For Entrepreneurship and Economic Growthmentioning
confidence: 96%
See 1 more Smart Citation
“…Urbano et al (2019b), for instance, identify that existing scholarship tends more often to investigate variables such as taxes, property rights, contracts, and political factors related to freedom. Zhai et al (2019) complement this view by observing that cultural values, networks, cognitive factors and market dynamics are, among others, the most frequent (informal) institutions that scholars examine. Based on these literature reviews, it is suggested that variables related to the environment that affects the entrepreneurial process, in which proxies for the five dimensions that Gnyawali and Fogel (1994) suggest, need further attention.…”
Section: Institutional Environment For Entrepreneurship and Economic Growthmentioning
confidence: 96%
“…Despite these advances, the extant literature still lacks empirical explorations on Gnyawali and Fogel's (1994) dimensions that influence entrepreneurial activity (Aparicio et al 2016a). This scarcity of literature is also identified in the work of Boettke and Coyne (2009), Elert and Henrekson (2017), Urbano et al (2019b), andZhai et al (2019), who analyze and classify the existing amount of research about institutions and entrepreneurship. Accordingly, these authors find that most of the studies focus on the distinction between formal and informal institutions, in which the former are more explored than the latter.…”
Section: Institutional Environment For Entrepreneurship and Economic Growthmentioning
confidence: 99%
“…The institutional economics framework offered by North [14,15] may contribute to our understanding of how culture affects productive activities such as green entrepreneurship. Although there have been a number of studies analyzing formal institutions as initial steps toward entrepreneurial activity (see Bjørnskov and Foss [38], Urbano et al [18], and Zhai et al [39] for thorough literature reviews), it has been argued that informal institutions are more influential within society [18,40,41]. An additional conclusion relates to interactions between formal and informal institutions, with many regulations potentially working better depending on the cultural values of society [42].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Drawing on this approach, some authors suggest that institutional factors determine entrepreneurial activity (Aidis, Estrin, and Mickiewicz 2008;Bras and Soukiazis 2019;Bruton et al 2010;Hayton, George, and Zahra 2002;Salimath and Cullen 2010;Thornton et al 2011;Welter 2005). Others suggest that procedures for starting a business affect entrepreneurship negatively (van Stel, Storey, and Thurik 2007;Zhai et al 2019), and that risk-taking and creativity encourage entrepreneurial behavior Weinberger et al 2018).…”
mentioning
confidence: 99%
“…According to Baumol (1990), Sobel (2008), and Urbano and Aparicio (2019), productive entrepreneurial activity is encouraged more in those developed countries where wellestablished institutions exist, as compared to developing countries, where there is a lack of formal institutions. Although there should be a complementarity between formal and informal institutions to support entrepreneurial activity (Su 2020;Zhai et al 2019), the intentionality of progressing while helping others through entrepreneurship may stem from the society's culture (Stephan and Uhlaner 2010;. Therefore, it is in informal institutions where SPO is embedded.…”
mentioning
confidence: 99%